Uji Kualitatif Kandungan Rhodamin-B Dalam Saus Sambal Yang Beredar Di Pasar Baru (Regional) Mamuju - Oileri Tikirik, Wita; Afdaliah, Zulfah; Nur, Akbar; Tarnoto, Tenny; Sahrianti S, Nini (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
Rhodamin-B is harmfrul to human health because of its chemical properties and heavy metal contains chlorine compounds (Cl).Cholorine compounds are halogen compounds that are dangeraous and reactive if ingested, these commpounds will try to achieve stabiliy un the body by binding to other compounds in the body, this is what is toxis to the body. This resereach is a qualitative descriptive study with laboratory testing using the Rhodamin test kit Rhodamin-B to determine the presence or absence of Rhodamin-B content in chill sauce circulationg in the baru mamuju market. The results of this study indicate that 4 sampels of chili sauce circulationg in baru (Regional) mamuju were declared not no contain Rhodamin-B. It is recommended that furthere research be investigated by further testing method namely quantitative test.